Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kepuasan Kerja PT. Silva Andia Utama - Syahla Friska Pratricia Arifin; Bachruddin Saleh Luturlean (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In the mining industry, qualified human resources (SDM) are needed to cope with complex challenges. The quality of human resources among them can be seen from job satisfaction. Based on the absence data with a non-explanatory status indicates the dissatisfaction experienced by the production staff. Other factors that affect job satisfaction are work discipline and work motivation. This research was conducted to analyse the influence of work discipline and motivation of work on the work satisfaction of the production staff of PT. Silva Andia Utama. The purpose of this study was to find out how the work disciplines and motivations of work influence on the satisfaction work of the staff of production PT. This research uses a method of quantitative approach with types of descriptive and causality research. Sampling using probability sampling techniques and the sample-taking method used is a saturated sample method, with the number of samplings respondents as much as 57 employees. Technical analysis of data using descriptive analysis and double linear regression analysis. The results of the description analysis showed that the work discipline as well as job satisfaction entered into the good category and the motivation of work entered in the category is quite good. The results of the analysis of the double lineary regression show that the working discipline and motivation have a positive and significant influence on the satisfaction of the work staff of production PT. Silva Andia Utama both partially and simultaneously. Keywords: Human Resources, Work Discipline, Work Motivation, Job Satisfaction